2011
DOI: 10.1371/journal.pone.0022930
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ubiquitination Sites by Using the Composition of k-Spaced Amino Acid Pairs

Abstract: As one of the most important reversible protein post-translation modifications, ubiquitination has been reported to be involved in lots of biological processes and closely implicated with various diseases. To fully decipher the molecular mechanisms of ubiquitination-related biological processes, an initial but crucial step is the recognition of ubiquitylated substrates and the corresponding ubiquitination sites. Here, a new bioinformatics tool named CKSAAP_UbSite was developed to predict ubiquitination sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 39 publications
1
142
0
3
Order By: Relevance
“…In this work, it would be difficult to prove definitively that a particular lysine residue is not ubiquitylated under any conditions. However, almost all researchers (Cai et al, 2012;Chen et al, 2011;Lee et al, 2011;Radivojac et al, 2010) of ubiquitylation prediction use a strategy in which any lysine residue that is not marked by any ubiquitylation information on the same protein is a non-ubiquitylation site. In addition, Radivojac et al (2010) concluded that this strategy did not significantly influence the prediction performance for a model of yeast.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, it would be difficult to prove definitively that a particular lysine residue is not ubiquitylated under any conditions. However, almost all researchers (Cai et al, 2012;Chen et al, 2011;Lee et al, 2011;Radivojac et al, 2010) of ubiquitylation prediction use a strategy in which any lysine residue that is not marked by any ubiquitylation information on the same protein is a non-ubiquitylation site. In addition, Radivojac et al (2010) concluded that this strategy did not significantly influence the prediction performance for a model of yeast.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
“…CKSAAP_UbSite was constructed by Chen et al (2011) for identifying ubiquitylation sites by using the composition of k-space amino acid pairs surrounding a query site with the assistance of a SVM. Recently, Cai et al (2012) presented a method based on multi-sequence features and the nearest neighbor algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination sites were predicted using CKSAAP UbSite web server (59). Pictorial 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 representations of structural motifs against the linear sequence were generated in the EMBL server PDBsum.…”
Section: Structure Assessmentmentioning
confidence: 99%
“…In 2011, University of Pittsburgh, Pennsylvania, pulmonologist Jay Kolls reported that mice genetically lacking the IL-17 receptor did not develop emphysema despite six months of exposure to cigarette smoke 9 . More recently, Kheradmand and collaborators at the MD Anderson Cancer Center in Houston, Texas, genetically engineered mice to overexpress one form of IL-17 -IL-17A -and then exposed these mice to cigarette smoke for four months 8 . The mice developed an especially severe form of emphysema along with producing more destructive proteases.…”
Section: Ken Garber Is a Freelance Science Writer Based In Ann Arbormentioning
confidence: 99%